Komparasi Material Lepas Sedimen Pantai sebagai Penerapan Project Based Research dalam mendukung Pembelajaran Sedimentologi - Nurul Awaliyah; Syaifa Luttha Hanora; Ikhsan Adevita; Rohima Sera Afifah (JURNAL TEKNOSAINS KODEPENA, 2026)
This research aimed to provide an overview of the variation in grain size sorting in beach sediment materials in the Manggar area and its surroundings. The research employed a Comparative analysis of rocks. The methodology applied was descriptive analytical, combining primary and secondary data. Primary data was obtained through field observations and direct testing using sieve tests with various sand grain sizes on the research objects. At the same time, secondary data was collected from literature studies sourced from journals related to grain size. This method was applied to obtain a comprehensive overview of the research object and answer the objectives that had been set. The deposits along the beach of the Manggar area were unconsolidated sediments, indicating variations in grain size in the sand fraction. Through this research, researcher aim to support development of student competence in sedimentology.